Sustainable livehoods : (International Development, 1999)
Supporting systematic analysis of proverty and its causes in a way that is holistic hence more realistic but also manageable. Promoting a wider and better informed view of the opportunities for development activities and their likely impact. Placing people and the priorities they define firmly at the centre of analysis and objective setting.